. (2nd April 2013) - Unknown
<x xml:space="preserve">Abstract</x> The following article from Wind Energy, Vibrational analysis of the flexo‐torsional modes of the NREL 5‐MW reference wind turbine, by Alejandro D. Otero, Fernando L. Ponta and Lucas I. Lago, published online on April 2, 2013, in Wiley Online Library (wileyonlinelibrary.com), has been retracted by agreement between the authors, the journal Editors in Chief, Rebecca Barthelmie and Scott Schreck and John Wiley & Sons Ltd. The retraction has been agreed due to its overlap with Chapter 5: 'Structural Analysis of Complex Wind Turbine Blades: Flexo‐ Torsional Vibrational Modes', By Alejandro D. Otero, Fernando L. Ponta and Lucas I. Lago', DOI: 10.5772/51142 in 'Advances in Wind Power', Edited by Rupp Carriveau, ISBN 978‐953‐51‐0863‐4, Published: November 21, 2012.